Case Report: The application of amplatzer vascular plug to repair aortic dissection intimal tears and false lumen - Ruihua Li; Yang Liu; Jianjun Jiang (Frontiers in Cardiovascular Medicine, 2024)
In recent years, significant advancements have been made in endovascular therapy for aortic dissection, resulting in the development of various treatment methods. Nevertheless, there is a contentious discussion regarding the suitability of different treatment methods for addressing the unique features of individual lesions. Specifically, the matter of whether the presence of small intimal tears or multiple distal tears requires extensive aortic coverage with graft stents, which may block the blood supply to important organs, intercostal arteries, or lumbar arteries, remains unresolved. Further research is necessary to determine the need for complex fenestrated or branched endovascular aortic repair (F/B-EVAR) in the management of chronic post-dissection aneurysms involving visceral arteries. Our report highlights the successful endovascular repair of three patients with aortic dissection, encompassing one Stanford A type and two Stanford B types. Utilizing the Amplatzer Vascular Plug (AVP) alone or in combination with the coil embolization technique, we achieved favorable clinical outcomes. This article aims to provide valuable insights and new perspectives on the tailored management of aortic dissection by conducting a comprehensive examination of the subtle differences in the treatment processes and techniques applied to these three patients.